2006
DOI: 10.1080/14622200601047900
|View full text |Cite
|
Sign up to set email alerts
|

Smoking cessation via the Internet: A randomized clinical trial of an Internet intervention as adjuvant treatment in a smoking cessation intervention

Abstract: Internet interventions for smoking cessation are ubiquitous. Yet, to date, there are few randomized clinical trials that gauge their efficacy. This study is a randomized clinical trial (N= 284, n= 140 in the treatment group, n= 144 in the control group) of an Internet smoking cessation intervention. Smokers were randomly assigned to receive either bupropion plus counseling alone, or bupropion and counseling in addition to 12 weeks of access to the Comprehensive Health Enhancement Support System for Smoking Ces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
135
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(139 citation statements)
references
References 10 publications
3
135
0
1
Order By: Relevance
“…Although there is a dearth of published studies of interventions to increase live donor transplantation, Rodrigue et al published a recent clinical trial that randomized renal transplant candidates to homebased education about live donor transplantation performed by a health educator (38). After a single home-based intervention, transplant candidates were more likely to express willingness to talk to potential donors, to have more potential live donor (39,40). Our study used a novel endpoint and measured relevant attributes but has several limitations.…”
Section: Discussionmentioning
confidence: 99%
“…Although there is a dearth of published studies of interventions to increase live donor transplantation, Rodrigue et al published a recent clinical trial that randomized renal transplant candidates to homebased education about live donor transplantation performed by a health educator (38). After a single home-based intervention, transplant candidates were more likely to express willingness to talk to potential donors, to have more potential live donor (39,40). Our study used a novel endpoint and measured relevant attributes but has several limitations.…”
Section: Discussionmentioning
confidence: 99%
“…Of the 18 studies [42][43][44][45][46][48][49][50][51][52][53][54][55][56][57][58][59][60] that randomised smokers, nine investigated the effectiveness of interventions matched for programme length, [42][43][44][45][46][48][49][50][51] six compared interventions of varying programme lengths [52][53][54][55][56][57] and two trials examined the effectiveness of RPI adjuncts to cessation programmes. 58,59 Thirteen of these trials verified self-reported smoking abstinence with carbon monoxide measurements, 42,45,46,[48][49][50][52][53][54][55]57,58,60 one used saliva thiocyanate, …”
Section: Studies Randomising Smokersmentioning
confidence: 99%
“…58,59 Thirteen of these trials verified self-reported smoking abstinence with carbon monoxide measurements, 42,45,46,[48][49][50][52][53][54][55]57,58,60 one used saliva thiocyanate, 44 another saliva cotinine, 59 two verified abstinence with urine cotinine 43,56 and one used self-reported abstinence only. 51 …”
Section: Studies Randomising Smokersmentioning
confidence: 99%
“…However, there have been few evaluations of computer-assisted treatment, of any type, for the addictions. Much of this work has been done in the area of smoking, where several randomized trials of predominantly cognitive-behavioral interventions or self-help guidelines delivered via computers/internet have indicated positive effects on quit rates or attempts (27)(28)(29). Computerassisted brief motivational approaches and self-control training programs have shown promise in randomized controlled trials with problem drinkers (30,31) and college students (32).…”
Section: Introductionmentioning
confidence: 99%